Building And Completing Social Security System In Vietnam Today - Phạm Thị Hằng; Trịnh Vương Cường (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Khoa học Xã hội, 2012)
Over the past years, the State and Party have paid special attention to developing the social security system, considering this as a central factor in the development process of the country. During the 25-year development process, the social security system has been gradually finalised, making significant contribution to the national socio-economic stabilisation and development. However, the system still shows its weakness. In the article, the author focuses on analysing structure, function, tasks as well as compulsory institutions and operation principles of the social security system. This helps analyse the situation and assess strong points, weakness, causes and challenges for the process of building and completing the country’s social security. This also helps to promote some solutions to boost quality and operation effectiveness of the social security system in the industrilisation, modernisation and global integration process.